INTELLECTUAL POTENTIAL OF A REGION: APPRAISAL AND CONTROL TOOL IN INNOVATIVE ACTIVITY - O. Loseva (Управленческие науки, 2016)
In today’s economy, characterized by globalization, frequent crisis phenomenon, acceleration of scientific-technical progress innovative activity takes on special significance. The basis for innovative activity is intellectual potential which is a set of intellectual resources and attained intellectual results, including innovation. The article presents the structure of intellectual potential of a region, reveals the main elements of the methodology for its evaluation. A model of intellectual potential appraisal based on statistical approach is offered. The quality of intellectual potential of a region is understood as the combination of its two characteristics, i. e. the level of development and sustainability of functioning according to the indicators aggregate in the system of regions, the indicators being specified by the matrix. It is suggested that the entropy of particular indicators should be taken into account when calculating summary rating in order to increase ranking reliability.The tool of control over the region’s intellectual potential quality in innovation is shown, the former comprising the following tools of diagnostics and monitoring: 1) system of indicators of intellectual potential characterizing its state in the areas that are crucial for effective innovation, i. e. innovation and entrepreneurship, research and cultural-educational ones; 2) procedure of the intellectual potential quality estimation, based on determination of integral rankings, carried out according to the level of development and stability of the indicator values of a particular region within the system of other regions, and taking into account indicators entropy; 3) factor analysis algorithm of the intellectual potential dynamics on the basis of the index method.The paper sets the guidelines for of use of the obtained results in the interests of the region’s innovation development and anticipated effects from their practical implementation: financial, budgetary, administrative, general economic effects.The conclusion is made that methodology for appraisal of intellectual potential and the tool of control over its quality can be effectively applied in order to stir up innovation in the region.